Estudo sobre o uso de dicionários escolares nas salas de 4º e 5º anos da rede municipal de Catalão-GO - Ribeiro, Cacildo Galdino (2014)
Studies conducted in Brazil have shown that the school dictionary is a didactic work that can contribute significantly with the process of lexical acquisition of student, but it is little used in schools. In this sense, the lexicographic proposals of school dictionaries must be aligned to the profile of the audience, for whom they are intended, with a view, therefore, aspects of micro and macroestructure. Therefore, the Ministry of Education (MEC) promoted, on the occasion of the National Plan of the Textbook – PNLD/2006, the provision of public schools with lexicographic collections to be used by the students of the first segment of elementary school. The collections offered by the Government were organized according to the evaluation and selection of dictionaries, carried out by the Commission of scholars and researchers, established by the MEC. It is from this context that this work verifies how and whether the school dictionaries offered by MEC are used in local government schools of Catalão-Go, particularly, in the fourth and fifth years. For both, this research presents brief considerations about matters related to the subject in question, for reasons connected with the Lexicography and Lexicology, such as some concepts of word, the types of dictionaries etc., in order to substantiate the analyses of corpus collected via questionnaires applied to teachers of these grades and informal conversations with professionals from the local government the Secretary of education of Catalão and with coordinators and principals of the participating schools. It is believed that the little use of dictionaries is linked to the lack of training courses for teachers in the area of the lexicon, so the results of this research can contribute to the elaboration of extension courses or specialization for teachers of the local government education.